Effects Of Semantics Of Pronunciation On Arabic Speech Understanding - An Application Study On Marriage Prohibition In Contemporary Exegeses Of the Holy Qur’an/ آثار دلالات المنطوق في فهم الكلام العربي - دراسة تطبيقية في تحريم النكاح بالرضاع في التفاسير المعاصرة للقرآن الكريم - Ahmad S Burhan; Fehmieh R Nawaya; Abdulaziz E Hajji; Ali M Asaad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The Arabic language is characterized by the diversity of semantics of its words, and the mastery of these semantics is a decisive factor in understanding Arabic speech. The research aimed to show the effect of the semantics of pronunciation in understanding speech. This aim was achieved by conducting an application study that extrapolates the sayings of contemporary interpreters about clauses of the verse of prohibition in Surat An-Nisa, which talk about the banning of marriage because of breastfeeding. This topic was chosen to conduct the application study on it due to its unique advantage: the two semantics of exact pronunciation and the three semantics of the non-explicit pronunciation in one clause of the same verse. A complete extrapolation of the sayings mentioned in the most significant contemporary interpretations of the Holy Qur’an about the understanding of the studied verse was conducted to determine the effect of the semantics of pronunciation in controlling the meanings of the words and to show how these semantics share the express of the desired purpose. Both analytical and critical methods were assumed. The results confirmed the importance of understanding the semantics of pronunciation in interpreting the noble verse. Through this understanding, it was possible to give preference between the sayings of the interpreters. The results also showed differences between the semantics of pronunciation regarding the strength and clarity of their expression. Moreover, they clarified the importance of the context in understanding the semantics and eliciting judgments. Because of the semantics of pronunciation in understanding the meanings of the texts, it is recommended to include them in Arabic language teaching curricula and to train learners on how to use and extract them from texts.